El Modelo De Atención Integral De Salud Familiar, Comunitario E Intercultural Y El Impacto En La Calidad De Satisfacción A Los Usuarios Externos Del Sector De Las Marianitas Del Área De Salud#16-Daule De La Provincia Del Guayas. - Cajas Carvajal, Christian Alberto (2015)
In Ecuador aims to improve the health status of the population, so now we have developed a model of comprehensive care of family, community and intercultural health (MAIS-IFC), the same that considers aspects such as prevention, accessibility and quality of care for the users of this service nationwide, which increases the degree of user satisfaction. This research has as main objective to analyze the impact on the quality of satisfaction of external users of the health area Marianitas # 16-Daule Guayas province in relation to compliance and application of the model of comprehensive health care industry family, community and intercultural, for which measured the degree of knowledge of administrative and medical staff, we have determined compliance with the indicators of quality of care in relation to standardized parameters defined in the MAIS-FCI and evaluated the impact on the satisfaction of external users with the data collected an institutional plan to improve user satisfaction was designed. This study was descriptive, field, cross as physical visits were made to the area of health # 16-Daule. We worked with a sample of 28 people and 32 administrative area of the health team, in addition to 355 patients admitted to hospital were surveyed. The main results it was observed that there is a link between compliance with the MAIS-IFC and user satisfaction as strengths which include increased technical and human quality staff primary care level of 83% related kindness and respect of auxiliary staff and nurses the score was 69.2%; and communication with staff (information level) had a value of 92.3% was also seen complaints about the lack of medicine and the lack of an inventory of goods.